Legal Basis For Diplomatic Asylum’s Eligibility - Ben Abderrezak Abdelnacer, Abdelnacer; Mimouni, Abdelhalim (My University, 2022)
This study deals with the concept of diplomatic asylum. The diplomatic asylum refers to a critical situation related to the flight of a political refugee to the territory of another country or to the headquarters of its diplomatic missions (consulate or embassy) within the country (taking Latin American countries as an example). It highlights the important legal basis for granting diplomatic asylum mainly: Humanitarian Considerations and the Consensual Basis.
المجلد 3العدد2
Keywords: Asylum ; Consulate ; Diplomatic Asylum ; Diplomatic Mission ; Embassy ; Legal Basis